1978
DOI: 10.1111/j.1600-0722.1978.tb00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorhexidine‐coated dressing on plaque formation after gingivectomy

Abstract: abstract— The aim of this clinical study was to evaluate the effect on plaque formation after gingivectomy when the periodontal dressing Coe‐Pak® was coated with chlorhexidine hydrochloride powder. The study indicates that no additional plaque‐inhibiting effect can be obtained by this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…O'Neil (1975) reported the varied antimicrobial effect of five different dressings in vitro, and Haugen et al (1977) demonstrated a decrease in antibacterial activity of dressings with time. Bay & Langebaek (1978) showed no enhanced plaque inhibition with chlorhexidine impregnated dressings. In con-trast, Piuss et al (1975), found a dressing impregnated with chlorhexidine reduced bacterial colonisation of the teeth.…”
mentioning
confidence: 88%
“…O'Neil (1975) reported the varied antimicrobial effect of five different dressings in vitro, and Haugen et al (1977) demonstrated a decrease in antibacterial activity of dressings with time. Bay & Langebaek (1978) showed no enhanced plaque inhibition with chlorhexidine impregnated dressings. In con-trast, Piuss et al (1975), found a dressing impregnated with chlorhexidine reduced bacterial colonisation of the teeth.…”
mentioning
confidence: 88%
“…Furthermore, the possibility that bacterial plaque may be found between the dressing and the tissue surface also questions the effectiveness of periodontal packs. However, reduction of postoperative pain and facilitation of healing process have been achieved with the incorporation of antiseptics (Ashoe-Jorgensen et al, 1974;Addy and Douglas, 1975;Bay and Langebaek, 1978) and antibacterial agents (Romanow, 1964;Heaney et al, 1972;Breloff and Caffesse, 1983) in periodontal dressings. In addition, chlorhexidine mouthrinse is a widely used adjunct in periodontal therapy due to its antibacterial effects.…”
mentioning
confidence: 99%
“…Numerous reports have published data regarding the benefits of addition of various chlorhexidine formulations to periodontal dressings (28-29-30-31-32, 34). Clinical trials supporting the use of periodontal dressing are tabulated in Table III.…”
Section: Types Of Periodontal Dressingsmentioning
confidence: 99%